2015
DOI: 10.1111/ajsp.12113
|View full text |Cite
|
Sign up to set email alerts
|

Individual social capital and the implementation of entrepreneurial intentions: The case of Russia

Abstract: The current research hypothesized that individual social capital facilitates the implementation of one's intention to start a business. The research samples were drawn from a sample of 2061 adult respondents: a sub-sample of 269 adults who stated their intention to start their own business during the next two years ('intenders') and a matching sub-sample of 270 who said they did not intend to do so ('non-intenders'). The study shows that the 'intenders' possessed greater individual social capital. These resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
5
22
0
1
Order By: Relevance
“…Other scholars (Lin, 2001;Verhaeghe & Tampubolon, 2012) have focused on social capital as a source of the individual social resources which allow people to achieve their goals. Individual social capital means social connections and relations with surrounding people, which ultimately allow the person to more effectively adapt to the social environment (Tatarko & Schmidt, 2016) and, as a consequence, achieve greater life satisfaction.…”
Section: The Conceptual Model Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Other scholars (Lin, 2001;Verhaeghe & Tampubolon, 2012) have focused on social capital as a source of the individual social resources which allow people to achieve their goals. Individual social capital means social connections and relations with surrounding people, which ultimately allow the person to more effectively adapt to the social environment (Tatarko & Schmidt, 2016) and, as a consequence, achieve greater life satisfaction.…”
Section: The Conceptual Model Of the Studymentioning
confidence: 99%
“…Therefore, this social capital will be considered at the level of individual analysis (Lin, 2001), referred to as "individual social capital" (Verhaeghe & Tampubolon, 2012). We define individual social capital as the social connections and relations with others that ultimately allow a person to adapt to the social environment more effectively (Tatarko & Schmidt, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Start-up success is embedded in a broad set of skills and expertise of the entrepreneur such as human and financial capital and access to networks (Gompes & Leruer, 2001). However, start-ups usually cannot build on the entrepreneur's human and financial capital alone (Tatarko & Schmidt, 2016). Therefore, online and offline networks are crucial for them to get the necessary financial and knowledge resources needed to succeed (Wu, 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, examining individual-level social capital, Tatarko and Schmidt (2016) showed that it facilitates the execution of an individual's intention to start a business. Besides social capital at the individual level, Kwon and Arenius (2010) examined social capital at the country level and showed how it impacts entrepreneurial opportunity perception.…”
Section: Social Capital and Entrepreneurshipmentioning
confidence: 99%
“…For example, some studies have explored the effects of individual-and country-level social capital on entrepreneurial activities (Kwon & Arenius, 2010;Tatarko & Schmidt, 2016). …”
mentioning
confidence: 99%